2022
DOI: 10.1186/s13054-022-03924-2
|View full text |Cite
|
Sign up to set email alerts
|

Repeated endo-tracheal tube disconnection generates pulmonary edema in a model of volume overload: an experimental study

Abstract: Background An abrupt lung deflation in rodents results in lung injury through vascular mechanisms. Ventilator disconnections during endo-tracheal suctioning in humans often cause cardio-respiratory instability. Whether repeated disconnections or lung deflations cause lung injury or oedema is not known and was tested here in a porcine large animal model. Methods Yorkshire pigs (~ 12 weeks) were studied in three series. First, we compared PEEP abrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Additionally, they promote high transpulmonary pressure and large tidal volume, both linked to lung damage. Animal studies have shown that abrupt deflation, following a sustained lung inflation, could induce acute lung injury mediated by acute left ventricular decompensation as a result of increased left ventricular preload and afterload [ 11 , 15 ]. Finally, diaphragmatic contractions may elicit lung injury irrespective of VT changes, secondary to a phenomenon known as ‘Pendelluft’.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they promote high transpulmonary pressure and large tidal volume, both linked to lung damage. Animal studies have shown that abrupt deflation, following a sustained lung inflation, could induce acute lung injury mediated by acute left ventricular decompensation as a result of increased left ventricular preload and afterload [ 11 , 15 ]. Finally, diaphragmatic contractions may elicit lung injury irrespective of VT changes, secondary to a phenomenon known as ‘Pendelluft’.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been described in patients with vigorous inspiratory effort against airway obstruction and is also called post-obstructive pulmonary edema [23]. In animal studies, abrupt deflation after sustained inflation, which is associated with a dramatic decrease in intrapulmonary pressure, could cause acute lung injury mediated by the significant vascular leakage and acute decompensation of the left ventricle [24,25]. These data imply that lung injury may also be caused by the abrupt and large change in intrathoracic pressure.…”
Section: Excessive Lung Perfusionmentioning
confidence: 95%
“…A similar experimental plan was performed in a porcine model (Katira et al, 2022), wherein the increase in LVEDP was not…”
Section: Abrupt Deflationmentioning
confidence: 99%
“…Modulation of mechanical ventilation to optimize the CP interactions may help reduce forces on both sides of alveolar capillary membrane. Moreover, limiting lung deflations due to ventilator disconnections not only improves lung function but may also reduce lung injury from atelectasis and vascular forces (Maggiore et al, 2003;Maggiore et al, 2013;Katira et al, 2022).…”
Section: Translational Implicationmentioning
confidence: 99%
See 1 more Smart Citation